The Islamic perspective to employee green behavior: a preliminary study / Siti Rohana Daud … [et al.] - Daud, Siti Rohana; Mukapit, Mukhiffun; Sehat, Nani Shuhada; Jogeran, Jumaelya; Suhaime, Intan Liana; Ahmad, Khaizie Sazimah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
This paper drives to explore and elaborate on the benefits of initiating green approach at workplace to enhance and improve healthier and greener working environment within the organizational context. Heightenedglobal warming and the severity of climate change has placed the world in apredicament and the organization as a workplace may have its own contributing elements to these phenomena , thus this study focuses on ways to contribute for the betterment of our environment and at the same time enhance work performance by going green. The initiation of green approach at workplace is geared towards a sustainable and greener outcome based contribution, as a feature of the organization.. Data were collected from several researchers whose work on green related studies and research have shown profound arguments and impact on the employees and their performance at workplace. The results of studies from the Islamic perspective and the related views, as well as other western research are found to uphold and express optimism towards the idea of implementing green initiation at workplace as it had shown significant outcome in individual employee’s growth psychologically, emotionally and physically and also enhance the organizational performance, financially, technologically and in several other areas.